Cuticular hydrocarbon reception by sensory neurons in basiconic sensilla of the Japanese carpenter ant - Watanabe, Hidehiro; Ogata, Shoji; Nodomi, Nonoka; Tateishi, Kosuke; Nishino, Hiroshi; Matsubara, Ryosuke; Ozaki, Mamiko; Yokohari, Fumio (Frontiers in Cellular Neuroscience, 2023)
To maintain the eusociality of a colony, ants recognize subtle differences in colony-specific sets of cuticular hydrocarbons (CHCs). The CHCs are received by female-specific antennal basiconic sensilla and processed in specific brain regions. However, it is controversial whether a peripheral or central neural mechanism is mainly responsible for discrimination of CHC blends. In the Japanese carpenter ant, Camponotus japonicus, about 140 sensory neurons (SNs) are co-housed in a single basiconic sensillum and receive colony-specific blends of 18 CHCs. The complexity of this CHC sensory process makes the neural basis of peripheral nestmate recognition difficult to understand. Here, we electrophysiologically recorded responses of single basiconic sensilla to each of 18 synthesized CHCs, and identified CHC responses of each SN co-housed in a single sensillum. Each CHC activated different sets of SNs and each SN was broadly tuned to CHCs. Multiple SNs in a given sensillum fired in synchrony, and the synchronicity of spikes was impaired by treatment with a GAP junction inhibitor. These results indicated that SNs in single basiconic sensilla were electrically coupled and shared CHC responsibilities. Quantitative analysis indicated that the Japanese carpenter ants have the potential to discriminate chemical structures of CHCs based on the combinational patterns of activated SNs. SNs of ants from different colonies exhibited different CHC response spectra. In addition, ants collected from the same colony but bred in separate groups also exhibited different CHC response spectra. These results indicate that the peripheral sensory mechanism is important for discrimination between nestmate and non-nestmate ants.